1987
DOI: 10.1128/iai.55.2.288-292.1987
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation and interaction of secretory immunoglobulin A and a calcium-dependent parotid agglutinin for several bacterial strains

Abstract: Previous studies have suggested that both secretory immunoglobulin A (sIgA) and various nonimmunoglobulin salivary glycoproteins are capable of agglutinating a variety of bacteria. The present study was designed to compare the nature of the agglutinins for Streptococcus mutans and Salmonella typhimurium in parotid saliva and colostrum. S. mutans was aggregated by saliva and colostrum, whereas S. typhimurium was aggregated only by saliva as detected by a spectrophotometric method. The principal salivary aggluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 20 publications
2
43
0
Order By: Relevance
“…However, the indication in Lhe present study that the interaction between the SMGs and the streptococci has a largely calciumdependent, electrostatic basis, does not support this concept. Results of experiments by RUNDEGREN & ARNOLD (20) also showed that the bacterial agglutinating activity of saliva is mainly dependent upon a calcium-dependent non-immunoglobulin agglutinin. Furthermore, an experiment employing fluorescent antibody on isolated SMGs showed no reaction with the SMGs, only with bacterial contaminants {Rolla.…”
Section: Discussionmentioning
confidence: 87%
“…However, the indication in Lhe present study that the interaction between the SMGs and the streptococci has a largely calciumdependent, electrostatic basis, does not support this concept. Results of experiments by RUNDEGREN & ARNOLD (20) also showed that the bacterial agglutinating activity of saliva is mainly dependent upon a calcium-dependent non-immunoglobulin agglutinin. Furthermore, an experiment employing fluorescent antibody on isolated SMGs showed no reaction with the SMGs, only with bacterial contaminants {Rolla.…”
Section: Discussionmentioning
confidence: 87%
“…After chromatography on Sepharose 4B (2.0 by 120 cm), active fractions were pooled, lyophilized, and stored at -20°C. Some preparations of agglutinin were purified as described by Rundegren and Arnold (45).…”
Section: Methodsmentioning
confidence: 99%
“…This agglutinin has been isolated from both parotid and submandibular saliva of humans, and shown to be distinct from secretory IgA and mucins (Williams and Gibbons, 1975;Malamud, 1985). The agglutinin has been purified by both column chromatography (Demuth et al, 1988) and bacterial affinity (Rundegren and Arnold, 1987). The isolated glycoprotein is approximately 40% carbohydrate and 60% protein (Ericson and Rundegren, 1983).…”
mentioning
confidence: 99%